Peningkatan Kemampuan Musikal pada Siswa-Siswi SMP Katolik Giovanni Kupang Melalui Kegiatan Ektrakurikuler Band Sekolah - Paskalis Romanus Langgu; Soni Oktofianus Mapada; Ervina Magdalena Funan; Dominikus Dionisius Temdy Tukan; Hildagardis Mamo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Merdeka Belajar Kampus Merdeka (MBKM) is a form of implementation of the dharma of devotion that provides work and learning experiences for students in community empowerment. One form of activity in the MBKM program is an activity to improve musical abilities for students of Giovanni Kupang Catholic Middle School through extracurricular school band activities. This activity aims for students to be able to improve their musical abilities through extracurricular band activities. The stages of implementing the devotion start from observation, core activities of providing material in theory and practice and documentation. Based on the results of observations and interviews, one of the factors that causes the lack of students' musical skills is the lack of musical activities carried out at school and the lack of musical practice in the classroom. The results of this training show an increase in students' abilities in playing musical instruments like electric guitar, keyboard, bass guitar as well drums and improving singing abilities.